A new method for repairing internal carotid artery rupture in skull base surgery: a case report and review of the literature - Li, Jia-Nan; Wen, ZhongCheng; He, Jiajie; Zhou, Minghao; Liu, Jun; Liu, Qingbo; Li, Fuyong; Cao, Peng; Yu, Chunyong; Liang, Guobiao (Frontiers in Surgery, 2025)
Internal carotid artery rupture during skull base surgery represents a rare yet catastrophic complication, with limited reports documented in the literature. In this article, we describe a case of ICA rupture encountered during supratentorial craniotomy for recurrent pituitary adenoma resection. The rupture was successfully managed through a novel microsurgical repair technique, achieving complete tumor resection. A 48-year-old female presented with a history of progressive visual impairment in both eyes for the past two years, 14 years after the initial pituitary adenoma resection. Reoperation was performed through the original pterional incision. During tumor dissection, sudden rupture of the right ICA occurred. Immediate cervical common carotid artery compression was applied, followed by microsurgical hemostasis using absorbable gelatin sponge and cottonoids. Temporary aneurysm clips were placed to achieve proximal flow control, allowing full exposure of the ICA rupture site. A small autologous muscle patch was used to cover the defect, and microsurgical repair was performed using a figure-of-eight suture technique. Complete hemostasis and total tumor resection were achieved. Postoperative digital subtraction angiography confirmed the patency of the ICA without stenosis, and the patient exhibited no neurological deficits postoperatively. This case combined the advantages of muscle tissue application and surgical suturing. The use of autologous muscle tissue promoted platelet aggregation, reducing tension at the rupture site and preventing further vascular tearing, while rapid suturing minimized blood loss. Additionally, the proficient collaboration and coordination with the anesthesiologist and surgical assistants were vital for controlling the intraoperative hemorrhage and ensuring prompt repair.